Developing the Global Self: A Developmental-Psychological Analysis of Identity Negotiation and Adaptation in Intercultural Learning Environments - Muhammad Habib Nabil Hermansyah; Rayhan Firasyan Riyadi; Firman Alief Firdausy Hidayat; Rafiqi Nur Ahmadi Hidayat; Ummi Masrufah Maulidiyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This systematic literature review examines the psychological processes underlying global identity development in intercultural learning environments. Using thematic synthesis methodology, this study analyzes peer-reviewed articles published between 2023-2024 from databases including PsycINFO, PubMed, ERIC, and Web of Science. Drawing from developmental and cross-cultural psychology frameworks, the review synthesizes recent research on identity negotiation, psychological adaptation, and global self-concept formation among individuals navigating multiple cultural contexts. Findings reveal that global identity development is a dynamic process influenced by bicultural identity integration, psychological adjustment mechanisms, and environmental factors. Successful identity negotiation correlates with positive psychological outcomes, including enhanced well-being, academic achievement, and intercultural competence. This review contributes to understanding how educational systems can support healthy global identity formation through culturally responsive pedagogical approaches.